Age at school entry: How old is old enough? - Elizabeth Dhuey (IZA World of Labor, 2016)
Laws on age at school entry affect student achievement and often change for a number of reasons. Older students are more mature and ready to learn. This can have positive impacts on academic, employment, and earnings outcomes. The costs of holding children back include another year of childcare expenses or income forgone by the caregiver parent. Entering the workforce one year later also has implications for lifetime earnings and remittances to governments. School-entry policies could be a useful tool in increasing student achievement, but the short- and long-term impacts need to be better understood.
Keywords: I21; 330; education; age; relative age; kindergarten; redshirting